Green Entrepreneurship In Theory And Practice - Chellig, Abdeldjalil; Bakdi, Malika (جامعة الوادي University of Eloued, 2025)
The environment is extremely important for human existence, it must be integrated into the heart of business strategies. It is recognized that entrepreneurship is vital for economic development. Thus, it plays an important role in social development, as well as a catalyst for growth. The emergence of sustainable development is considered a parameter that drives the creation of green entrepreneurship. Around the 1990s, the concept has rapidly developed. In recent years, an increasing number of business leaders have integrated environmental issues in their business strategies. Algeria does not escape this global trend; it has displayed key measures to encourage entrepreneurship, and especially green entrepreneurship. In this study, we will present an overview of entrepreneurship in Algeria.
Green Entrepreneurship in Theory and practice: Perspectives for Algeria
مقال
Keywords: Environment; Green growth; Green entrepreneurship; Green economy; Sustainable development